Legitimation of political and legal institutions: social dynamic approach to legal reality - Калюжний, Р. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Scientific review of the monograph V. Neizvestny "Self-organization of legal reality and legitimacy of the Fundamental Law."